맞춤형 정보공개 서비스를 위한 이용자 요구 분석 및 지능화 방안: 문화예술 공공기관을 중심으로 - 최정원; 나정호; 오효정; Choi, Jungwon; Na, Jeong Ho; Oh, Hyo-Jung (Journal of Records Management & Archives Society of Korea, 2021)
The public's interest in the information disclosure system is increasing daily in line with the democratic cause of a transparent government and demands of the people to build on their right to know. Meanwhile, as society develops, the importance of culture and art in the quality of life is also increasing. Under these circumstances, culture and arts institutions are seeking to contribute to the expansion of the people's participation by providing timely and useful information and programs with high interest. Accordingly, this study intends to propose customized information services by analyzing the user's needs for information on public institutions in culture and arts and reflecting on the information disclosure service. For this purpose, three public institutions of in the culture and arts will be selected as representative examples to collect and cross-analyze the list of disclosed information received by users over a year. Furthermore, the requirements for the automation and intelligence of information disclosure tasks were summarized, and specific improvement plans were proposed for customized information services. 정보공개제도는 투명한 정부라는 민주적 대의와 국민의 알 권리 향상이라는 시대적 요구에 따라 국민들의 관심이 나날이 높아지고 있다. 한편 사회가 발전함에 따라 국민의 삶의 질 향상에 있어 문화예술의 중요성 역시 점차 높아지고 있다. 이러한 배경 하에 많은 문화예술기관에서는 시의적절하고 유용한 정보와 관심도 높은 프로그램을 제공함으로써 국민의 문화예술 활동 참여 확대에 기여하는 방안을 모색하고 있다. 이에 본 연구는 공공기관에 대한 이용자 정보요구를 파악하여 지능적으로 정보공개 서비스에 반영하는 맞춤형 정보서비스를 제안하고자 한다. 이를 위해 3개의 국내 문화예술 공공기관을 대표 사례로 선정, 1년여의 기간 동안 실제 이용자들이 접수한 정보공개청구 목록과 검색어를 수집 및 교차 분석함으로써 이용자 관심도와 정보요구 양상을 파악한다. 나아가 정보공개 업무의 자동화 및 지능화를 위한 필요사항을 정리하고 이용자 요구 중심 정보서비스를 위한 구체적인 개선방안을 제언하였다.